2022
DOI: 10.1021/acsinfecdis.2c00006
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Potent SARS-CoV-2 Blocking Lectin Protein

Abstract: The COVID-19 (coronavirus disease-19) pandemic affected more than 180 million people around the globe, causing more than five million deaths as of January 2022. SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2), the new coronavirus, has been identified as the primary cause of the infection. The number of vaccinated people is increasing; however, prophylactic drugs are highly demanded to ensure secure social contact. A number of drug molecules have been repurposed to fight against SARS-CoV-2, and som… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 58 publications
(86 reference statements)
3
32
0
Order By: Relevance
“…The IC 50 values of the weight concentration (1.6 μg·mL −1 for both the strains), which is typically used for comparisons among antibodies, were comparable to the value of 0.71 μg·mL −1 obtained for FRIL by a similar PRNT assay [ 19 ]. The values were also comparable to the 0.42 μg·mL −1 obtained for GRFT based on a quantitative reverse‐transcription/real‐time PCR (qRT‐PCR) assay [ 20 ], and much stronger than the 50–100 μg·mL −1 for CLEC4G or CD209C obtained by qRT‐PCR [ 18 ]. Therefore, PhoSL is among the most potent lectins for inhibition of SARS‐CoV‐2 infection.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…The IC 50 values of the weight concentration (1.6 μg·mL −1 for both the strains), which is typically used for comparisons among antibodies, were comparable to the value of 0.71 μg·mL −1 obtained for FRIL by a similar PRNT assay [ 19 ]. The values were also comparable to the 0.42 μg·mL −1 obtained for GRFT based on a quantitative reverse‐transcription/real‐time PCR (qRT‐PCR) assay [ 20 ], and much stronger than the 50–100 μg·mL −1 for CLEC4G or CD209C obtained by qRT‐PCR [ 18 ]. Therefore, PhoSL is among the most potent lectins for inhibition of SARS‐CoV‐2 infection.…”
Section: Resultssupporting
confidence: 68%
“…C‐type lectins related to the above, namely, CD209 antigen‐like protein C (CD209C) and C‐type lectin domain family 4 member G (CLEC4G), were found to show high affinities with S protein and inhibitory effects on SARS‐CoV‐2 infection [ 18 ]. These activities have also been demonstrated for lectins of non‐mammalian origins, namely, Flt3 receptor‐interacting lectin (FRIL) isolated from hyacinth bean [ 19 ], and Griffithsin (GRFT) isolated from red alga [ 20 ]. To use these lectins as drugs, the off‐target effects, including blood coagulation, should be reduced.…”
Section: Introductionmentioning
confidence: 99%
“…[ 28 ] The antiviral effect of Griffithsin is known to emerge from the phenomenon of GRFT binding to surface glycoproteins of enveloped viruses and blocking the viral internalization step as a result. [ 27 , 29 ] The antiviral effect of GRFT on several enveloped viruses such as human immunodeficiency virus‐1, [ 30 ] SARS‐CoV, [ 31 ] and middle east respiratory syndrome coronavirus [ 32 ] was shown previously through the interactions of GRFT with their surface proteins gp‐120, and S‐proteins, respectively. In a recent study, GRFT was also shown to be prevalent for binding the spike protein of SARS‐CoV‐2 virus and blocking its entry to Vero6 cell lines and IFNAR−/−mouse models.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study, GRFT was also shown to be prevalent for binding the spike protein of SARS‐CoV‐2 virus and blocking its entry to Vero6 cell lines and IFNAR−/−mouse models. [ 29 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation